Un conservatoire botanique adapté au territoire guyanais : comment intégrer connaissances scientifiques et connaissances traditionnelles? - Marie Fleury (Éditions en environnement VertigO, 2012)
Despite the widely accepted idea of an area covered with a homogeneous forest, french Guiana is actually very heterogeneous in both distribution of species and forest landscapes. We will discuss the various usual ways for exploration of plant biodiversity and their development through the introduction of a botanical conservatory in french Guiana. Two examples will be developed : the state of knowledge and acquisition strategies for forest tree species with emphasis on the fragmented appearance of the forest area ; and the study of species listed as "useful", associated with human activities, in particular plants related to traditional agriculture, medicinal plants and exotics, whose presence is related to human habitat, old or new. The establishment of the botanical conservatory in the Guiana Region, supported by the « Region Guyane » and by the Ministry of the environment, allows us to set up a structure integrating scientific knowledge and traditional knowledge. This mediator between the state, local collectivities, research organizations, associations and communities, could become a real tool for biodiversity governance for Guiana, and also a platform for international collaboration on the scale of the Guiana Shield.